Variability and pharmacological potential of bajakah (Spatholobus sp.) as an indigenous medicinal plant: a review - Mahfudh, Nurkhasanah; Utami, Dwi; Nashihah, Siti; Ahda, Mustofa; Andika, Andika; Sabilla, Giriani Ayu (Intelektual Pustaka Media Utama, 2024)
Bajakah (Spatholobus sp.) is an indigenous Indonesian plant that has been traditionally used as medicine, especially in Kalimantan Island, Indonesia. The variability and potential of bajakah as a traditional Indonesian medicinal plant have attracted research attention. This review article describes the traditional use, distribution, and pharmacological activity of bajakah. An integrative review method was employed, following procedures such as literature search, data analysis, and result presentation. Understanding the variations is important to understand the therapeutic potential and differences in active compound content among different types of bajakah. Furthermore, the chemical composition of bajakah has been identified, including alkaloids, flavonoids, tannins, saponins, and triterpenoids, which can potentially exhibit pharmacological effects and mechanisms of action associated with its traditional use. This review provided additional insights into the potential of bajakah as an herbal medicinal in the future. Therefore, this review article provides an overview of the traditional use distribution, and pharmacological activity of bajakah as a promising traditional medicine. Further research, including clinical studies, is needed to scientifically validate the therapeutic potential of bajakah and further understand the mechanisms of action and potential side effects associated with it.